2023
DOI: 10.1073/pnas.2215067120
|View full text |Cite
|
Sign up to set email alerts
|

White-tailed deer ( Odocoileus virginianus ) may serve as a wildlife reservoir for nearly extinct SARS-CoV-2 variants of concern

Abstract: The spillover of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from humans to white-tailed deer (WTD) and its ability to transmit from deer to deer raised concerns about the role of WTD in the epidemiology and ecology of the virus. Here, we present a comprehensive cross-sectional study assessing the prevalence, genetic diversity, and evolution of SARS-CoV-2 in WTD in the State of New York (NY). A total of 5,462 retropharyngeal lymph node samples collected from free-ranging hunter-harvested WTD d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…Since prior surveillance studies have reported RT-qPCR positivity rates of upwards of 30% in nasal swabs 4 and seropositivity rates of more than 40% 12,26 , it was initially surprising that no animals within the Vermont sample set were positive, especially during the 2022 season. However, recent work from Diel et al describing the spread of SARS-CoV-2 within deer in New York state during the 2021 and 2022 seasons showed only sporadic positives during 2021 and a significant increase (up to 20%) in the 2022 season 15 . Furthermore, the majority of positive cases were detected in the western half of New York and near New York City, the farthest regions geographically from the Vermont border 14 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since prior surveillance studies have reported RT-qPCR positivity rates of upwards of 30% in nasal swabs 4 and seropositivity rates of more than 40% 12,26 , it was initially surprising that no animals within the Vermont sample set were positive, especially during the 2022 season. However, recent work from Diel et al describing the spread of SARS-CoV-2 within deer in New York state during the 2021 and 2022 seasons showed only sporadic positives during 2021 and a significant increase (up to 20%) in the 2022 season 15 . Furthermore, the majority of positive cases were detected in the western half of New York and near New York City, the farthest regions geographically from the Vermont border 14 .…”
Section: Discussionmentioning
confidence: 95%
“…However, multiple recent studies in North America have shown that members of the Cervidae family are susceptible to SARS-CoV-2. We hypothesized that SARS-CoV-2 might be circulating in Vermont deer and wildlife, given the numerous reports of infections within wild deer populations 4,[9][10][11][12][13][14][15] , and laboratory infections showing vertical 16 and horizontal transmission 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Seven CoVs infect humans; two of the α-genus (the Duvinacovirus hCoVs 229E and the Setracovirus NL63) and five of the β-genus: the Sarbecoviruses severe acute respiratory syndrome (SARS)-CoVs 1 and 2, the latter responsible for a pandemic since 2019 [ 3 6 ]; the Merbecovirus Middle East respiratory syndrome (MERS) CoV; and the Embecoviruses hCoV-OC43 and -HKU1. Human CoVs have a zoonotic origin, with bats as key reservoir [ 7 ] and possibly other hosts [ 8 , 9 ]. Bat β-CoVs related to human CoVs belong to the Sarbecovirus , Nobecovirus , and Hibecovirus subgenera [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting in 2020, SARS-CoV-2 was found in white-tailed deer [WTD; 1,2]. By 2021, there was evidence of regional transmission in WTD through a combination of ongoing deer-to-deer and human-to-deer transmission [2][3][4][5]. Endemic transmission of SARS-CoV-2 in WTD could position these populations as reservoir hosts, posing risk for variant persistence [4,6], evolution of new variants [7,8], and spillback into human populations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Deer-to-deer transmission may occur within wild populations beyond the initial introduction period. Surveillance studies in WTD have shown persistence of SARS-CoV-2 alpha and gamma variants in populations 4-6 months after their peak circulation and extinction in the human population [4,5,17,18]. These data describing susceptibility and transmission capabilities of SARS-CoV-2 in WTD and the fact that WTD are abundant and share a variety of habitats with humans across the United States [19], highlight the need to understand potential infection dynamics of SARS-CoV-2 in WTD across the range of the species.…”
Section: Introductionmentioning
confidence: 99%